Lipids trigger a conformational switch that regulates Signal Recognition Particle (SRP)-mediated protein targeting - Stjepanović, Goran; Kapp, Katja; Bange, Gert; Graf, Christian; Parlitz, Richard; Wild, Klemens; Mayer, Matthias P.; Sinning, Irmgard (The journal of biological chemistry, 2011)
Co-translational protein targeting to the membrane is mediated by the signal recognition particle and its receptor (FtsY). Their homologous GTPase domains interact at the membrane and form a heterodimer in which both GTPases are activated. The prerequisite for protein targeting is the interaction of FtsY with phospholipids. However, the mechanism of FtsY regulation by phospholipids remained unclear. Here we show that the N terminus of FtsY (A domain) is natively unfolded in solution and define the complete membrane-targeting sequence. We show that the membrane-targeting sequence is highly dynamic in solution, independent of nucleotides and directly responds to the density of anionic phospholipids by a random coil-helix transition. This conformational switch is essential for tethering FtsY to membranes and activates the GTPase for its subsequent interaction with the signal recognition particle. Our results underline the dynamics of lipid-protein interactions and their importance in the regulation of protein targeting and translocation across biological membranes.
Online verfügbar 3 Mai 2011, Artikelversion 4 Januar 2021
Gesehen am 24.10.2022